Laser therapy in dental specialties - Maria Betânia Lins Dantas Siqueira; Priscilla Suassuna Carneiro Lúcio; Maria Helena Chaves de Vasconcelos Catão (Editorial Ciencias Médicas, 2015)
Introduction: laser therapy has been used with great success in dental clinics, and constitutes an excellent option in current health care. Objective: determine the number of dentists specializing in laser therapy in the north / northeast of Brazil and identify the regions in the Brazilian territory where there is a greater demand for courses on laser therapy. Methods: adescriptive study was conducted based on the examination of secondary data available from the Brazilian Federal Council of Dentistry of the area, the services section and consultations, in the year 2013. Results were evaluated with the chi-square test and Fisher's exact test (significance level of 5 %). Results: the sample was composed of 29 professionals. In the regions analyzed, most professionals with specialization in laser therapy are general, non-specialized practitioners. It was found that the southeast stands out for its greater availability of certified courses on laser therapy, followed by the south and the north. No course about laser therapy was found in the northeast, despite the fact that there are more qualified professionals in that region than in the north. Laser therapy should not be defined as a new device in dental practice, but as a new therapeutic philosophy allowing biophysical interaction between light and biological tissue, thus providing better treatment and improving the quality of life of patients. Conclusions: alarger number of specialized professionals may be found in the south and southeast of Brazil, but an increase in their number is already noticeable in the northeast.